2018
DOI: 10.1111/bju.14209
|View full text |Cite
|
Sign up to set email alerts
|

Serenoa repens + selenium + lycopene vs tadalafil 5 mg for the treatment of lower urinary tract symptoms secondary to benign prostatic obstruction: a Phase IV, non‐inferiority, open‐label, clinical study (SPRITE study)

Abstract: We have shown that treatment with SeR-Se-Ly was not inferior to tadalafil 5 mg for improving IPSS and Q in men with LUTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Two trials with high RoB reported a non-significant reduction in TPV from baseline after tadalafil (-5.9%) and sildenafil (-3.9%) treatment [ 55 , 56 ]. PSA changes as reported in three trials were not significantly different from baseline (-8.6% -0%) [ 28 , 54 , 56 ]. There was no information on TZV or prostate perfusion parameters.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Two trials with high RoB reported a non-significant reduction in TPV from baseline after tadalafil (-5.9%) and sildenafil (-3.9%) treatment [ 55 , 56 ]. PSA changes as reported in three trials were not significantly different from baseline (-8.6% -0%) [ 28 , 54 , 56 ]. There was no information on TZV or prostate perfusion parameters.…”
Section: Resultsmentioning
confidence: 98%
“…The SPRITE study randomized men to tadalafil 5 mg or phytotherapy [ 54 ]. No change of TPV was observed in the tadalafil arm at 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, no significative differences between the two groups emerged at the 3rd month voiding subscore assessment (p = 0.06) while a statistically significant improvement at 6-month evaluation (6 [IQR: 3-9] vs. 9 [IQR: 6-11], p = 0.03) in the treatment group was recorded. Table 3 A significative improvement in Qmax (16.7 mL/s [IQR: [13][14][15][16][17][18][19]] vs. 11.3 mL/s [IQR: 10-15], p = 0.001) and Qave (14.2 mL/s [IQR: [10][11][12][13][14][15][16] vs. 12 mL/s [IQR 10-14], p = 0.05) were found at 6-month evaluation in the treatment group as compared to the control group. In terms of PVR, significant differences were detected at each follow up visit with the most relevant reduction of median PVR at 6-month assessment (102 cc [IQR: 91-116] vs. 127 cc [IQR: 98-139], p = 0.02), (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the different kinds of extraction still limit the correct interpretation of the available data [17]. Currently, SeR represents the most commonly used phytotherapeutic compound for BPH management [18] and the only one actually recommended for well-established use by the Committee on Herbal Medicinal Products (HMPC). Its effectiveness in prostate size reduction and urinary frequency improvement was also confirmed by two systematic reviews and meta-analyses [10,19].…”
Section: Discussionmentioning
confidence: 99%